(untitled) (PANGEEA, 2025)
Expanded polystyrene (EPS) generates an environmental problem as a result of a slow biodegradation process, the idea of this project is to motivate the polluting agents to make an integrated management of solid waste, offering a reuse of this material. This work aims to address the reuse of EPS in the field of construction, in the manufacture of concrete and several materials as a partial substitute for natural aggregates. This material has favorable mechanical and thermal insulation properties for the construction industry and can reduce the use of other materials from exhaustible sources without neglecting the quality of a new product, thus saving natural resources. The new materials that have recycled polystyrene in their composition, being friendly to the environment and having at the same time an economic compensation, can arouse the interest of companies producing construction materials.